Performance measurement and cost accounting: are they complementary or competing systems of control? - Mohr, Zachary T. (2016)
In the public administration literature, research on performance measurement has recognized the important place of cost accounting in relation to performance. Extant research, such as the North Carolina Benchmarking Program, supports the proposition that performance and cost accounting naturally complement each other to increase trust in performance information and increase organizational learning. Other statements about cost accounting suggest that performance measurement and cost accounting compete as systems of control. This research uses general cost accounting plan information and performance measurements in the budgets of large U.S. cities to test the competing and complementary control relationship at the organizational and service levels. It finds that performance measurements and cost accounting are negatively related at the service level, which supports the competing control system hypothesis. At the organizational level, performance and cost accounting are positively related but not at traditional levels of significance. - Reproduced.
Keywords: Cost accounting; Performance appraisal